Cerebellar cognitive affective syndrome after acute cerebellar stroke - Abderrakib, Anissa; Ligot, Noemie; Naeije, Gilles (Frontiers in Neurology, 2022)
Introduction The cerebellum modulates both motor and cognitive behaviours, and, a cerebellar cognitive affective syndrome (CCAS) was described after cerebellar stroke in 1998. Yet, a CCAS is seldom sought for, due to lack of practical screening scales. Here, we aimed at assessing both the prevalence of CCAS after cerebellar acute vascular lesion and the yield of the CCAS-Scale (CCAS-S) in acute stroke setting. Materials and Methods All patients admitted between January 2020 and January 2022 with acute onset of cerebellar ischemic or hemorrhagic first stroke at the CUB-Hôpital Erasme and who could be evaluated by the CCAS-S within a week of symptoms onset were included. Results Cerebellar acute vascular lesion occurred in 25/1580 patients. All patients could complete the CCAS-S. A definite CCAS was evidenced in 21/25 patients. Patients failed 5.2 ± 2.12 items out of 8 and had a mean raw score of 68.2 ± 21.3 (normal values 82-120). Mostly failed items of the CCAS-S related to verbal fluency, attention and working memory. Conclusions A definite CCAS is present in almost all patients with acute cerebellar vascular lesion. CCAS is efficiently assessed by CCAS-S at bedside test in acute stroke settings. The magnitude of CCAS likely reflects a cerebello-cortical diaschisis.